Digital next‐generation sequencing of cell‐free DNA for pancreatic cancer. Issue 4 (22nd March 2021) - Takano, Shinichi; Fukasawa, Mitsuharu; Shindo, Hiroko; Takahashi, Ei; Fukasawa, Yoshimitsu; Kawakami, Satoshi; Hayakawa, Hiroshi; Kuratomi, Natsuhiko; Kadokura, Makoto; Maekawa, Shinya; Enomoto, Nobuyuki
Abstract: Background and Aim: The clinical applicability of digital next‐generation sequencing (dNGS), which eliminates polymerase chain reaction (PCR) and sequencing error‐derived noise by using molecular barcodes (MBs), has not been fully evaluated. We evaluated the utility of dNGS of cell‐free DNA (cfDNA) in liquid biopsies obtained from patients with pancreatic cancer. Methods: Fifty‐eight patients with pancreatic cancer undergoing endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) were included. Samples were subjected to sequencing of 50 cancer‐related genes using next‐generation sequencing (NGS). The results were used as reference gene alterations. NGS of cfDNA from plasma was performed for patients with a mutant allele frequency (MAF) >1% and an absolute mutant number > 10 copies/plasma mL in KRAS or GNAS by digital PCR. Sequence readings with and without MBs were compared with reference to EUS‐FNA‐derived gene alterations. Results: The concordance rate between dNGS of cfDNA and EUS‐FNA‐derived gene alterations was higher with than without MBs ( p = 0.039), and MAF cut‐off values in dNGS could be decreased to 0.2%. dNGS using MBs eliminated PCR and sequencing error by 74% and 68% for TP53 and all genes, respectively. Overall, dNGS detected mutations in KRAS (45%) and TP53 (26%) and copy number alterations in CCND2, CCND3, CDK4, FGFR1, and MYC, which are targets of molecular‐targeted drugs. Conclusions: dNGS of cfDNA using MBs is useful for accurate detection of gene alterations even with low levels of MAFs. These results may be used to inform the development of diagnostics and therapeutics that can improve the prognosis of pancreatic cancer. Abstract : Recently, a minimally invasive method called liquid biopsy (LB), which obtains genetic information of a tumor from blood sample, has attracted attention; however, sequence‐ and/or PCR‐derived errors become a problem in next‐generation sequencing (NGS) analysis. This study investigated the effect of molecular barcodes (MBs) for reducing sequence‐ or PCR‐derived errors on analyzing low mutant allele frequencies (MAFs) in cell‐free DNA (cfDNA) compared with gene alterations detected in tissue samples from patients with pancreatic cancer and we considered digital NGS of LB cfDNA using MBs useful and expect that our results will be an important contribution to the development of diagnostics and therapeutics that can improve the prognosis of pancreatic cancer.